PENGARUH SAWIT SEBAGAI PENGGERAK PEREKONOMIAN INDONESIA TERHADAP PELESTARIAN HUTAN - Eddy Soegiarto (LEGALITAS : Jurnal Ilmiah Ilmu Hukum, 2017)
This research is carried out in East Kalimantan in the location of Palm Horticulure especially in Sangatta, East Kutai Regency 400 km from Samarinda for one month. The method of the research is qualitative  by taking news from some media, interview and observation. The results of it are that the government of Indonesia has to get action that, (1) To face Europion attack on palm industry policy by diplomacy, (2) Together with Malaysia have had the of their own, (3) Europe will disturb the home affairs of Indonesia on palm industry,(4) In order not to excute the deforestry the Indonesian government     has to make some public policies on public welfare in the surround of forest people. (5)To empower the palm production and its under benefits by making sinergy with other ministries and others in promoting palm. The suggestions are ,(1) To make diplomacy actions with Europian on palm industry carefully, (2) Indonesia together with  Malaysia have to adapt the international standard, (3) Europian has to be countered wisely if they disturb the palm industry and agriculture affairs, (4) Indonesian Government has to be creative to take way out or solusion to stop the deforestry, (5)The minister of Agriculture has to make sinergy with others to empower the palm and the forestest in order to create many new jobs ,(6) Indonesian Government has to arry ut the regulation N0.41 /1999 about Forestry.